Synthesis and Biological Studies of Schiff Bases Derived from 4-methyl 7-Ethylcoumarin - Kazem, Muntather Hossam; Ahamed, Luma S. (Iraqi Journal of Science, 2024)
New 7-ethyl-4-methyl coumarin derivatives bearing an azo methene group (C=N) were synthesized by a four-step process. The reaction between 7-ethylphenol and ethyl acetoacetate in the presence of sulfuric acid afforded 7-ethyl-4-methylcoumarin 1 in 90% yield. Nitration conditions (nitric acid and sulfuric acid) were then applied to product 1 to produce 6-nitro-7-ethyl-4-methycoumarin 2 and 8-nitro-4-methyl-7-ethylcoumarin 3. The temperature, the amount of starting materials, and the time of reaction were essential factors in obtaining a high yield of isomer 2 compared to the second isomer 3. The nitro groups at compounds 2 and 3 were then reduced with iron metal in an acidic medium to form the corresponding amino compounds 4 and 5, which were converted to Schiff base derivatives 6-17 via reaction with different substituted aromatic aldehydes. The synthesized compounds were characterized by FT-IR, 1H NMR, and 13C NMR spectroscopy. Evaluating the biological activities of the synthetic compounds was carried out against two bacteria: gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) at 1×10-3 M; compound 15 showed a broad spectrum against these two types of bacteria compared to Vancomycin and Amikacin and against fungi compared to nystatin as a standard drug, but compound 7 showed stronger activities against fungi than the other synthesized compounds. In contrast, the rest of the compounds showed moderate activity against fungi compared with the same standard drag; in the antioxidant study, some new compounds showed powerful antioxidants compared with ascorbic acid as a stander reference by calculating the IC50. Compound 8 showed very good results as an antioxidant agent compared with the same standard.